Regular Cervical Cancer Screening for Iranian Women: Facilitators and Barriers - mansoureh refaei; zohreh khakbazan; nahid Dehghan Nayeri (Kerman University of Medical Sciences, 2020)
Introduction: Regular cervical cancer screening is an effective strategy to reduce the incidence and mortality rate of this disease. Therefore, the present study aimed to explain facilitators and barriers to performing regular Pap smear tests in Iranian women. Methods: This qualitative study was performed in 2017 in medical centers in Hamadan. The participants in this study were 23 women and 8 health care workers who were selected through purposive sampling. The inclusion criteria were the willingness to participate in the study and having the ability to communicate properly. The data were collected using in-depth semi-structured interviews and analyzed using the qualitative content analysis method with MAXQDA10 software. Results: Three main concepts were recognized as facilitators and barriers to regular Pap smear testing: (1) Belief vs. disbelief in the possibility of cancer control and treatment, (2) Priority vs. non-priority of health in life, and (3) Ability vs. inability to overcome the challenges ahead. Conclusion: Given the results of the study, it is necessary to establish policies to increase people's sensitivity to testing and the dominance of screening culture in society. Health officials also need to support training programs to promote women's understanding of the importance and impact of early diagnosis in controlling and treating cervical cancer and to develop and implement programs to reduce or eliminate financial, time, and emotional barriers.